An optimal harvest maturity model for 'Minneiska' apple fruit based on the delta-absorbance meter. Issue 5 (2nd September 2020) - DeLong, John; Harrison, Peter; Harkness, Lisa
ABSTRACT: A hand-held, chlorophyll content meter [the delta absorbance (DA) meter] was used to develop an optimal harvest maturity model for 'Minneiska' apples ( Malus domestica Borkh ). Fruit from four commercial orchards in the Annapolis Valley, Nova Scotia, Canada, were sampled weekly (25 fruit per location) over eight consecutive harvests during the 2011–2013 growing seasons. At each harvest, 60 fruit were measured for their DA value ( IAD ), mass, firmness, titratable acidity (TA), soluble solids content (SSC), red skin colouration, starch-to-sugar conversion and internal core ethylene concentration. Following 3–3.5 months of refrigerated air storage at 3.5°C, samples were removed and assessed for fruit bruising, skin greasiness, rot and physiological disorders. Peel chlorophyll content was strongly and positively correlated with epidermal IAD measurements. IAD values declined significantly during fruit ripening and were negatively related to harvest week. The optimal harvest period was identified by aligning 'at harvest' IAD, fruit quality and 'post-storage' disorder data with the corresponding harvest week. IAD averages associated with harvests having high commercial fruit quality demarcated the optimal harvest boundaries. As the IAD values declined during fruit maturity, the upper boundary value of 0.26 was defined as 'when to begin harvest', while the lower boundary value of 0.12 was deemed 'when to end harvest' for longer-term storage.